Gray space and default mode network-amygdala connectivity - Harris, Julia C.; Liuzzi, Michael T.; Cardenas-Iniguez, Carlos; Larson, Christine L.; Lisdahl, Krista M. (Frontiers in Human Neuroscience, 2023)
Introduction: Aspects of the built environment relate to health factors and equity in living conditions, and may contribute to racial, ethnic, or economic health disparities. For example, urbanicity is linked with negative factors including exposure to gray space (e.g., impervious surfaces such as concrete, streets, or rooftops). While there is existing research on access to green space and urbanicity on some mental health and cognitive outcomes, there is limited research on the presence of gray space linked with cognitive functioning in youth. The goal of this study was to investigate the link between gray space and amygdala-default mode network (DMN) connectivity.Method: This study used data from the ABCD Study. Participants (n=10,144; age M = 119.11 months, female = 47.62%) underwent resting-state fMRI acquisition at baseline. Impervious surfaces (gray space) were measured via the Child Opportunity Index (COI). To examine the relationship between presence of gray space and -amygdala-DMN (left/right) connectivity, we employed linear mixed effects models. Correlations were run between amygdala-DMN connectivity and internalizing and externalizing symptoms. Finally, post-hoc sensitivity analyses were run to assess the impact of race.Results: More gray space, adjusting for age, sex, and neighborhood-level variables, was significantly associated with increased left amygdala-DMN connectivity (p=0.0001). This association remained significant after sensitivity analyses for race were completed (p=0.01). No significant correlations were observed between amygdala-DMN and internalizing or externalizing symptoms.Discussion: Findings suggest gray space was linked with increased left amygdala-DMN connectivity, circuits that have been implicated in affective processing, emotion regulation, and psychopathology. Thus gray space may be related to alterations in connectivity that may enhance risk for emotion dysregulation. Future investigation of these relationships is needed, as neuroimaging findings may represent early dysregulation not yet observed in the behavioral analyses at this age (i.e., the present study did not find significant relationships with parentreported behavioral outcomes). These findings can help to inform future public policy on improving lived and built environments.